Trimetazidine has Promising Preventive Effects on Experimental Chronic Pancreatitis Rat Model - Kaplan, Mustafa; Karakaya, Arif; Tanoğlu, Alpaslan; Yıldırım, Muhammet; Önal Taştan, Yeşim; Çırak, Zafer; Küçükodacı, Zafer (Turkish Journal of Gastroenterology, 2022)
Background: It was aimed to evaluate the preventive efficacy of trimetazidine in an experimental chronic pancreatitis rat model. Methods: Chronic pancreatitis model was accomplished with caerulein and alcohol administration. In the study, 40 female Sprague Dawley rats were randomized into 5 groups containing 8 animals in each. Group 1 (chronic pancreatitis); group 2 (chronic pancreatitis+low-dose trimetazidine group); group 3 (chronic pancreatitis+high-dose trimetazidine group); group 4 (placebo group (chronic pancreatitis+saline)); group 5 (sham group). 24 hours after the last injection, all animals were sacrificed. Tumor necrosis factor-alpha, transforming growth factor-β, malondialdehyde, and glutathione peroxidase levels were tested in blood samples. Histopathologic examinations were conducted by a senior pathologist who was unaware of the group allocations. Results: Results of biochemical parameters of the trimetazidine groups (groups 2 and 3) were significantly favorable compared with the chronic pancreatitis group (group 1) (P < .05). The difference between the low-dose- and the high-dose trimetazidine group (group 3) was significant in terms of blood tests (P < .05). The difference between the low-dose trimetazidine group and the chronic pancreatitis group was not significant in terms of histopathologic scores (P > .05); however, the difference was significant between the high-dose trimetazidine group and the chronic pancreatitis group (P < .05). Conclusions: To the best of our knowledge, this current research is the first study that evaluates trimetazidine’s efficacy in the chronic pancreatitis rat model. Trimetazidine has affirmative preventive properties in the chronic pancreatitis course.